(untitled) (Economics and region, 2025)
This article examines the current state, development trends, and structural characteristics of Ukraine’s foreign trade with the European Union, highlighting both existing challenges and emerging opportunities. It provides a comprehensive analysis of the main factors shaping trade flows, including the ongoing process of economic integration, the significant impacts of military conflicts and logistical constraints, regulatory and policy changes, as well as the progressive adoption of European quality and technical standards. Special attention is given to the dynamics of exports and imports of goods and services, the evolving composition of trade flows, shifts in sectoral structures, and the role of key trading partners in supporting Ukraine’s economic resilience and stability. The study also explores how these factors influence Ukraine’s ability to diversify exports, improve competitiveness, and respond to external shocks in the global market. The research identifies strategic directions for enhancing trade development, such as increasing the share of high value-added products, fostering the integration of Ukrainian enterprises into European production chains, and strengthening institutional, regulatory, and governance frameworks to improve trade efficiency and market access. Moreover, the article emphasizes the critical importance of modernizing transport and logistics infrastructure, adopting best practices in trade facilitation, and implementing policy measures that support sustainable economic growth. It underlines that effective cooperation with EU partners and compliance with European standards can serve as key drivers for long-term economic stability and competitiveness. The findings offer valuable insights for business leaders, and academic researchers interested in foreign trade strategies, international economic cooperation, and the adaptation of national trade policies to global and regional challenges. By highlighting the dynamics of trade, the benefits of adopting modern standards, and concrete practical measures for deeper European integration, this study provides a solid foundation for strategic decision-making aimed at promoting Ukraine’s sustainable growth, resilience in international markets, and enhanced global competitiveness